The Sustainability of Home Industry Businesses in Enhancing Family Welfare From The Perspective of Islamic Economics, Focusing on Case Study of Tent Business - Basri Mahendra Hasibuan; Arif, Muhammad; Daulay, Aqwa Naser (Jurnal Manajemen Bisnis, 2024)
The purpose of this study is to analyze the home industrial enterprises maintain, starting by examining the institutional, social, and economic aspects. Methodology used in pene; This is qualitative with the Multi Dimensional Scaling (MDS) approach used in field research to create a more nuanced picture of real-world situations. The research was conducted in Tanjung Pasir Village, South Kualuh District, North Labuhanbatu Regency, North Sumatra Province. The primary source of data in this study is consumers. Meanwhile, secondary data was collected by watching interviews with business people in the home industry. The results of the study show that: 1) The sustainability of Pak Ajay Ahmad's tempe business in Tanjung Pasir Village is proven: the institutional dimension for the sustainability of household industry business management has an index of 7.14%; The average value of this sustainability index is 7.25 or in the range of 50.00 – 74.00 (quite sustainable); The social dimension of status is quite sustainable at 6.33%. 2) The economic dimension is the dimension with the highest level of sustainability, while the social dimension has the lowest level. The tempeh business sector in Tanjung Pasir Village has twenty-one characteristics. 3) Unstable and operational raw material prices (economic dimension), lack of support for MSMEs from local and village governments (social dimension), air pollution in tempe boiling, and waste management (institutional dimension) have the highest attribute sensitivity values.